Saving Renaissance and Reformation: History, Grammar, and Disagreements with the Dead - Fasolt, Constantin (Religions, 2012)
Renaissance and Reformation used to serve historians as the main terms with which to refer to European history from roughly 1300-1600. Today those terms are commonly replaced with early modern history, and the periodization of European history into ancient, medieval, and modern periods itself is looking increasingly suspect. There are good reasons for those changes. But they obscure both the significance of disagreements dividing the living from the dead and the significance of grammar, in the fundamental sense of grammar advanced by Wittgenstein, for treating such disagreements. Renaissance and Reformation have the advantage of doing just the opposite: they confront us with both those disagreements and the significance of grammar. That makes them very much worth keeping.